Financial crises and shadow banks: A quantitative analysis - Matthias Rottner (Deutsche Bundesbank, 2022)
Motivated by the build-up of shadow bank leverage prior to the financial crisis of 2007-2008, I develop a nonlinear macroeconomic model featuring excessive leverage accumulation and endogenous financial crises to capture the observed dynamics and to quantify the build-up of financial fragility. I use the model to illustrate that extensive leverage makes the shadow banking system runnable, thereby raising the vulnerability of the economy to future financial crises. The model is taken to U.S. data with the objective of estimating and analyzing the probability of a run in the years preceding the financial crisis of 2007-2008. According to the model, the estimated risk of a run was already considerable in 2005 and kept increasing due to the upsurge in leverage. Using counterfactual scenarios, I assess the impact of alternative monetary and macroprudential policy strategies on the estimated build-up of financial fragility.
Keywords: E32; E44; G23; 330; Financial crises; leverage; credit boom; nonlinear estimation